Design and development of a PID-controlled home air quality monitoring and purification system - Josamae Salas; Allain Jessel Macas (Innovation in Engineering, 2025)
Asthma continues to be a major health concern in the Philippines, with about one in ten people living with the condition. Among its common triggers are fine airborne particles such as PM2.5 and PM10, which can easily aggravate symptoms and affect day-to-day living. In response to this problem, we developed a home-based air quality management system intended to help individuals with asthma maintain safer indoor conditions. The system was equipped with a Proportional-Integral-Derivative (PID) controller, which allowed the purifier to respond more intelligently by tracking air quality in real time and adjusting its operation before conditions became unsafe. To test this feature, we set up a prototype in a bedroom and introduced small amounts of smoke to simulate pollution. In both setups—one with PID control and one without—the purifier successfully reduced particle levels and brought the Air Quality Index (AQI) back to its baseline of 79–81. The key difference, however, was that the PID-controlled system reacted ahead of time, activating the purifier before the thresholds were crossed. This shortened the period of exposure to poor air quality and produced more stable results overall. These findings demonstrate that incorporating a PID controller can enhance the reliability and effectiveness of home-based air purifiers, providing practical support for individuals managing asthma at home.